The Use of Moodle-based Learning Management System (LMS) on MATE (Media Ajar Teori Evolusi). (February 2020) - Syara, Y; Anggoro, BS; Handoko, A; Haka, N B; Kesumawardani, A D; Hidayah, N
Abstract: The goal of this research is to identify students' responses and see the feasibility of MATE ( Media Ajar Teori Evolusi ). This research is Research and Development. The subjects of the research were students of the sixth semester of Biology Education Department in the academic year of 2019. The ADDIE model (analysis, design, development, implements, and evaluation) was used as the design of the research. The developed product is declared as feasible because of its efficiency, light-weight, and compatibility. The students can construct their ideas. The developed product facilitates knowledge construction through the interactive online instrument. This is the first developed Moodle-based learning management system (LMS) on MATE ( Media Ajar Teori Evolusi ). It can help the lecturers to be more structured in teaching to achieve the goals of learning. Based on the validation conduction by experts, the overall result is 85, 5% and students response in the trial to get an 88% percent-rate average. Judging from the overall result, the learning media is declared as feasible and appropriate to be used.